Exploring coping strategies of emergency medical technicians against COVID-19 stress: a qualitative study - Parvaresh-Masoud, Mohammad; Abdollahyar, Asma; Molavi-Taleghani, Yasamin; Salahi, Sahar; Farahmandnia, Hojjat (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic has been shown to cause enormous psychological burden among health care workers, including first responders. However, the psychological well-being of first responders, essential in the fight against COVID-19 pandemic, has often been ignored. This qualitative study aimed to explore the coping strategies used by EMTs to manage stress during the pandemic.The research was designed as a qualitative study, utilizing a thematic analysis framework. Semi-structured interviews were conducted with 15 EMTs from a single geographic area between September 2022 and December 2022. The data were analyzed using Braun and Clarke analytic techniques, and this study used Lincoln and Guba's to assess the reliability of the data.Results: Four main coping strategies emerged from the data: seeking social support, practicing self-care, utilizing coping mechanisms, and finding meaning and purpose in work. EMTs sought support from both professional and personal sources, engaged in physical and emotional self-care, used humor and distraction as coping mechanisms, and found meaning and purpose in helping others and growing as professionals.Based on the extracted results from the study on EMTs in Iran, it can be concluded that the importance of social support cannot be overstated, as it serves as a crucial buffer against the negative effects of stress and trauma. The findings suggest that addressing the social and emotional needs of EMTs is important for promoting their mental health and well-being during the pandemic.